(untitled) (Konferensiyalar | Conferences, 2024)
The purpose of this article is to describe reflective technology for teaching foreign languages. The article analyzes various points of view on the definition of the concept of “reflection”, considered by scientists of philosophy, psychology, and pedagogy, and proposes the author’s definition of reflection from the point of view of methods of teaching foreign languages. Reflection on the purpose of implementation is described: reflection on the mood and emotional state of students, reflection on the assimilation of the content of educational material by students, reflection on the form of student activity.